Perfumed nightmare - Tahimik, Kidlat; Flower Films (Firm). (El Cerrito, Calif Flower Films, 1999)
This semi-autobiographical fable tells the story of a young Filipino born in 1942 (during the Occupation), his awakening to, and reaction against, American cultural colonialism.
Title in Tagalog: Mababangong bangungot.
Originally released as a motion picture in 1977.
Camera, Hartmut Lerch.
Mang Fely, Dolores Santamaria, Georgette Baudry, Kidlat Tahimik.
VHS format.
Keywords: Tahimik, Kidlat -- Drama; Filipinos -- Biography -- Drama; Motion pictures -- Philippines; Philippines -- History -- 1946-1986 -- Drama; Philippines -- Civilization -- Foreign influences -- Drama; Philippines -- Relations -- United States -- Drama; United States -- Relations -- Philippines -- Drama; Philippines -- Social conditions -- Drama